Cold molecular gas outflow encasing the ionized one in the Seyfert galaxy NGC 3281 - de Oliveira Bruno Dall’Agnol de; Storchi-Bergmann Thaisa; Morganti Raffaella; Riffel Rogemar A.; Ramakrishnan Venkatessh (Oxford University Press, 2025)
We present ALMA CO (2-1) observations of the Seyfert 2 galaxy NGC 3281 at ∼100 pc spatial resolution. This galaxy was previously known to present a bi-conical ionized gas outflow extending to 2 kpc from the nucleus. The analysis of the CO moment and channel maps, as well as kinematic modelling, reveals two main components in the molecular gas: one rotating in the galaxy plane and another outflowing and extending up to ∼1.8–2.6 kpc from the nucleus, partially encasing the ionized component. The mass of the outflowing molecular gas component is Mmol, out = (2.5 ± 1.6) × 106 M⊙ , representing ∼1.7–2 per cent of the total molecular gas seen in emission within the inner 2.3 kpc. The corresponding mass outflow rate and power are M˙out,mol = 0.12–0.72 M⊙yr−1 and E˙out,mol = (0.045–1.6) ×1040 erg s−1 , which translates to a kinetic coupling efficiency with the AGN power of only 10−4–0.02 per cent. This value reaches up to 0.1 per cent when including both the feedback in the ionized and molecular gas, as well as considering that only part of the energy couples kinetically with the gas. Some of the non-rotating CO emission can also be attributed to inflow in the galaxy plane towards the nucleus. The similarity of the CO outflow – encasing the ionized gas one and the X-ray emission – to those seen in other sources, suggests that this may be a common property of galactic outflows.